[Conducting Negotiations] - (:unkn) unknown (My University, 2012)
A meeting between Frank Walcott and other BWU (Barbados Workers' Union) members during wage negotiations with The Beverages Group. Handwritten in English on back: "Frank Walcott conducting negotiations with the Beverages Group - 1970s".
Landscape; black and white
Keywords: Walcott, Frank, Sir, 1916-; Barbados Workers' Union; Conference rooms; Meetings; Men